Система автоматического полива комнатных растений на базе Arduino - Чекубашева, В. А.; Глухов, О. В. (ХНУРЕ, 2019)
The development of electronic devices and systems are aimed primarily at improving the human life. This is achieved through the automation of household appliances, for example, domestic robots and "smart homes". Part of such a system can be an automatic irrigation device for indoor plants because there are not rare cases when a person does not have the opportunity to stay at home for a long time and monitor the state of flowers. This paper provides a description of such a system implemented on the basis of the Arduino Pro Mini microcontroller.
Keywords: Система автоматического полива комнатных растений на базе Arduino; Arduino